2020
DOI: 10.3390/brainsci10020107
|View full text |Cite
|
Sign up to set email alerts
|

CDKL5 Deficiency Disorder—A Complex Epileptic Encephalopathy

Abstract: CDKL5 deficiency disorder (CDD) is a complex of clinical symptoms resulting from the presence of non-functional CDKL5 protein, i.e., serine-threonine kinase (previously referred to as STK9), or its complete absence. The clinical picture is characterized by epileptic seizures (that start within the first three months of life and most often do not respond to pharmacological treatment), epileptic encephalopathy secondary to seizures, and retardation of psychomotor development, which are often observed already in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 60 publications
5
97
0
11
Order By: Relevance
“…Mutational analysis of orthologous genes in murine models also produces phenotypes which are clearly post-developmental, presenting only in adulthood 78 . Incidentally, just like CASK mutations, CDKL5 and MeCP2 mutations in males are associated with epileptic encephalopathy 2, 3 . These data raise the possibility that even in disorders such as Rett syndrome (MeCP2 mutation) and CDKL5 deficiency, the pathology may be neurodegenerative, as originally suggested by Andreas Rett 5 , but the clinical course may not be progressive in females due to the mosaic expression of the normal gene under heterozygous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational analysis of orthologous genes in murine models also produces phenotypes which are clearly post-developmental, presenting only in adulthood 78 . Incidentally, just like CASK mutations, CDKL5 and MeCP2 mutations in males are associated with epileptic encephalopathy 2, 3 . These data raise the possibility that even in disorders such as Rett syndrome (MeCP2 mutation) and CDKL5 deficiency, the pathology may be neurodegenerative, as originally suggested by Andreas Rett 5 , but the clinical course may not be progressive in females due to the mosaic expression of the normal gene under heterozygous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…So far, more than 265 variants have been reported in CDKL5, with mutations distributed all along the length of the protein [15]. Approximately 27% of these are considered pathogenic with many of these located in the catalytic domain [15].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the spatial expression of cdkl5, we performed in situ hybridization and found that cdkl5 is expressed in the brain from 1 dpf, in the muscle at 2 dpf, in the otic vesicles, eyes and heart from 2 dpf, in the kidneys from 3 dpf and in the developing spinal cord from 4 dpf (Supplementary Figure 1b). The brain, spinal cord, eyes, muscle, and kidneys represent tissues that are affected in patients carrying CDKL5 mutations [15] indicating that zebrafish may be a suitable model to study CDD pathogenesis.…”
Section: Cdkl5 Is Expressed During Early Zebrafish Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CDKL5 belongs to the serine-threonine kinase family and is widely distributed in the human body. The highest expression levels are in the peri- and postnatal stages of the nervous system, suggesting an important role in the process of brain development [ 23 ]. Recent studies demonstrated that CDKL5 regulates axon outgrowth, dendritic morphogenesis and synapse formation [ 24 ].…”
Section: Developmental and Epileptic Encephalopathy (Dee)mentioning
confidence: 99%